S34. EFFECTIVENESS OF INDIVIDUAL METACOGNITIVE TRAINING (MCT+) IN FIRST-EPISODE PSYCHOSIS. (18th May 2020) - Ochoa, Susana; Lopez-Carrilero, Raquel; Luisa Barrigon, Maria; Pousa, Esther; Grasa, Eva; González, Fermin; Monserrat, Clara; Gutierrez-Zotes, alfonso; Lorente, Esther; Barajas, Ana; Ruiz-Delgado, Isabel; Cid, Jordi; et al.
Abstract: Background: The individual Metacognitive Training (MCT+) is useful to reduce positive symptoms in people with schizophrenia, however less is known in people with first-episode psychosis (FEP). The aim of the study is to assess the effectiveness of MCT+ in FEP regarding symptoms and cognitive insight. Methods: A random clinical trial was performed with people with FEP from 10 clinical centers of Spain. One group received ten sessions of MCT+ and the other group received TAU. A total of 75 patients were included in the study, however only 40 finished the final assessment. Patients were assessed before treatment, post-treatment and 6 month follow-up. The assessment includes a battery of instruments for the main aims the Positive and Negative Syndrome Scale (PANSS) and the Beck Cognitive Insight (BCIS) will be analyzed. Repeated measures statistical test were used in order to assess differences between groups. Results: Both groups improved in Positive symptoms, in the MCT+ group the difference was 5.18 (SD=6.8) with a significance of p=0.002, while in the TAU group the difference was 3.38 (SD=4.9) with a significance of p=0.005. Regarding cognitive insight, in the MCT+ group patients improved in Self-reflectiveness, obtaining a score in baseline of 15.21 (SD=5.52) and 18 (SD=5.28) in post-treatment (p=0.017). The TAU group did not improve in any subscale of the BCIS. Discussion: The MCT+ seems to improve more in positive symptoms than TAU, although both interventions diminished the presence of these symptoms. The MCT+ improved the self-reflectiveness, being one of the important areas for the understanding of the daily social functioning in relation to other. Further analysis should be explored.